Is Mitochondrial Oxidative Stress the Key Contributor to Diaphragm Atrophy and Dysfunction in Critically Ill Patients? - Hongjie Duan; Hailiang Bai (Critical Care Research and Practice)
Diaphragm dysfunction is prevalent in the progress of respiratory dysfunction in various critical illnesses. Respiratory muscle weakness may result in insufficient ventilation, coughing reflection suppression, pulmonary infection, and difficulty in weaning off respirators. All of these further induce respiratory dysfunction and even threaten the patients’ survival. The potential mechanisms of diaphragm atrophy and dysfunction include impairment of myofiber protein anabolism, enhancement of myofiber protein degradation, release of inflammatory mediators, imbalance of metabolic hormones, myonuclear apoptosis, autophagy, and oxidative stress. Among these contributors, mitochondrial oxidative stress is strongly implicated to play a key role in the process as it modulates diaphragm protein synthesis and degradation, induces protein oxidation and functional alteration, enhances apoptosis and autophagy, reduces mitochondrial energy supply, and is regulated by inflammatory cytokines via related signaling molecules. This review aims to provide a concise overview of pathological mechanisms of diaphragmatic dysfunction in critically ill patients, with special emphasis on the role and modulating mechanisms of mitochondrial oxidative stress.